Bending Capacity Analysis of High-strength Reinforced Concrete Beams Using Environmentally Friendly Synthetic Fiber Composites. (2015) - Aulia, Teuku Budi; Rinaldi
Abstract: The research was conducted to determine the bending capacity of high-strength reinforced concrete beams with the addition of three environmentally friendly synthetic fibers i.e., polypropylene fiber, tie wire fiber, and used rubber tires fiber. Four beams with a dimension of 15 x 30 x 220 cm were tested, including a beam for specimen without fiber as comparison. Specimens were designed to experience bending failure. Yield point of steel (fy) used for flexural and shear reinforcement was 407.43 MPa. The diameter of flexural tensile reinforcement was 15.8 mm, 11.9 mm for the compressive reinforcement, as well as 11.9 mm for the shear reinforcement. Concrete proportion incorporated 8% silica fume and 1.5% polycarboxylate ethers based superplasticizer ViscoCrete 10 from the cement weight. The maximum diameter of split was 15.9 mm, having 550 kg/m3 cement content and w/c-ratio 0.30. The target compressive strength was 70 MPa for cylinder 15/30 cm. The results showed that all beams experienced flexural failure as planned. Addition of fibers enhanced the bending behavior significantly, especially in flexural capacity, deflection and ductility. In comparison with high-strength reinforced concrete beam without fibers, the beam with polypropylene fiber had the increase of flexural strength of 115.24%, deflection of 306.56% and ductility of 298.9%; with tie wire fibers resulted in the increase of flexural strength of 117.39%, deflection of 160.52% and ductility of 148.0%; as well as with used rubber tires fiber produced the enhance of flexural strength of 112.13%, deflection of 184.56% and ductility of 178.3%. It can be concluded that the use of such environmentally friendly synthetic fibers can reduce the brittleness of high strength concrete, in which polypropylene fiber had delivered the best value and can be used very effectively than the other two types of fibers.